Increasing Learning Achievement In Theme 4 Through Discovery Learning Method With Animated Image Media - Yunita Putriati (Universitas Sebelas Maret, 2020)
The purpose of this study was to increase student learning achievement on the two-dimensional figure material of my family theme (my family tree). This research is a classroom action research (PTK) which was conducted in 2 cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the first grade students of SD Muhammadiyah 8 Jagalan, Jebres District, Surakarta Regency in the academic year 2020/2021, totaling 27 students. Data collection techniques using observation, interviews, and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the Animated Image Media can increase student learning achievement on the two-dimensional figure material of my family theme (my family tree) in grade I SD Muhammadiyah 8 Jagalan, Jebres District, Surakarta Regency in the academic year 2020/2021 as evidenced by the percentage of completeness of learning achievement in cycle I of 55.6 % to 85.2% in cycle II